An Investigation of Agricultural Crisis Communications via Social Media - Courtney Gibson; Erica Irlbeck; Courtney Meyers; Cindy Akers; Peggy Price (Journal of Applied Communications, 2019)
How an agricultural organization handles the way the media reports a crisis can have an impact on the public’s perceptions of the organization, and sometimes the industry as a whole. The popularity of social media outlets as a venue for disseminating and gathering information and news makes the use of social media surrounding agricultural crises an important topic to investigate (Glynn, Huge, & Hoffman 2012; Hermida, 2010). A qualitative case study was conducted to investigate the use of social media tools during an agricultural crisis. The participants – communications directors, social media managers, and individuals with a close connection to the crisis under study – reported that social media was a major component of their communication efforts surrounding each crisis. Participants felt social media was very effective in these situations and had a major impact on their communication efforts. Although no participants reported using a structured social media strategy or crisis communication plan, they stated a need for such guidelines in the agricultural industry. From the data analyzed in this study, a model for using social media during a crisis situation, aimed specifically for use by those in the agricultural industry, was developed. This project was funded through the USDA's Beginning Farmers & Ranchers Project.
Keywords: crisis communications; social media; agricultural communications; grounded theory